The receipt of charges against the President of the Republic in the impeachment process in Brazil and the judicial control by the Supreme Federal Court (Euro-Latin American Journal of Administrative Law, 2024)
In the Brazilian constitutional system, the impeachment process against the President of the Republic may be initiated based on the commission of “crimes of responsibility,” a term referring to serious violations of the constitutional order, as defined by the Constitution and specified by statute. It is the duty of the Speaker of the Chamber of Deputies to conduct the initial review of the charges. This article examines whether the omission by the Speaker of the Chamber of Deputies to consider charges, or the decision to summarily dismiss them without deliberation by the full Chamber, may be subject to judicial review by the Supreme Federal Court (STF). To this end, the article investigates the relevant provisions of the 1988 Constitution and the impeachment legislation, with an analysis of the STF’s case law based on a survey of decisions issued between February 1990 and December 2022, using the search terms “impeachment and charges and ‘President of the Republic,’” resulting in 14 relevant cases. It finds that the STF has consolidated the understanding that the decision of the Speaker of the Chamber (and any omission to issue such a decision) is predominantly political in nature and not subject to judicial review — a position that weakens constitutional protections and the rule of law. The article argues that impeachment, although involving political bodies, constitutes a legal process of accountability for serious violations of the constitutional order, requiring observance of legality, due process of law, and the guarantee of access to justice. Thus, judicial review of omissions or arbitrary dismissals by the Speaker is essential to uphold the supremacy of the Constitution and to preserve democracy.
Keywords: impeachment; receipt of charges; President of the Republic; judicial review; Brazilian Supreme Federal Court.